Nutritional intake of elite male and female high jumpers during the general preparation phase - Veligekas, P.; Bogdanis, G. C.; Christofi, E. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The importance of physique in high jump is demonstrated by the prevalence of tall and extremely lean somatotypes among elite male and female high jumpers who also have a high muscle power to body mass ratio (O`Connor et al., 2007). Nutrition plays a key role in maintaining optimal body weight and body composition and also supports the requirements of heavy training (Stellingwerf et al., 2011). However, only a few studies have assessed the nutritional intake of high jumpers (Houtkooper et al., 2007). Therefore, the aim of this study was to investigate and compare the nutritional intake of elite male and female high jumpers during the general preparation phase of their annual training plan. Methods: Fifteen elite male and female high jumpers took part in the study (7 males: 1.86±0.08 m, 75.4±4.4 kg, personal best: 2.07±0.21 m and 8 females: 1.76±0.06 m, 59.4±5.6 kg, personal best: 1.67±0.15 m). Participants weighed and recorded their diet for 3 days (2 weekdays and 1 weekend day), during the general preparation phase. Nutrient intake was analyzed using custom-made software based on a standard nutritional database (Food Standards Agency, 2002). Statistical comparisons between male and female jumpers were made using independent t-test (p<0.05). Results: Average daily energy intake for male and female jumpers was 11.3±1.8 and 7.9±1.0 (p=0.12), respectively and was derived from carbohydrate by 40±3%, from fat by 41±2%, from protein by 18±2%, while alcohol represented less than 1%. Macronutrient intake per kg body mass did not differ between male and female jumpers and was 3.6±0.8 and 3.3±0.5 g/kg for carbohydrate, 1.6±0.1 and 1.3±0.1 g/kg for protein and 1.6±0.3 and 1.5±0.2 g/kg for fat. Discussion: The main finding of this study was that both male and female elite high jumpers followed a diet that was inadequate to support their daily training and recovery needs in terms of carbohydrate intake (Houtkooper et al., 2007). Although total energy intake was moderate to low, fat intake was in excess of what is recommended, while protein intake was within the range proposed to support intense training (Stellingwerff et al. 2011). The low energy and carbohydrate intake of elite high jumpers may be related with their perception that a low body weight is of paramount importance for success, but this may lead to sub-optimal training adaptations by affecting both duration and quality of training.